Potensi dan Tantangan Pemanfaatan Hutan Mangrove oleh Masyarakat Pesisir di Desa Bagan Serdang Kecamatan Pantai Labu - Romauli Situmorang; Mira Susila Warni; Meilinda Suriani Harefa (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2025)
The mangrove ecosystem is an ecosystem that has a very high ecological value. This ecosystem can protect the coastline from abrasion, serve as a habitat for various marine biota, and store a vast biodiversity. The purpose of this research is to analyze the potential of the mangrove ecosystem in Bagan Serdang Village, Pantai Labu District, and to identify the challenges of utilizing the mangrove ecosystem in Bagan Serdang Village, Pantai Labu District. This study uses a qualitative descriptive method by conducting direct observations, interviews, and documentation. The results of this research indicate that the mangrove potential in Bagan Serdang Village is quite good; however, the community has not fully understood the benefits of the mangrove forest due to limited knowledge, community awareness, and the lack of training and outreach provided by the local government and related agencies.